Application of Urf in Islamic banking and conventional bank - Abdul Aziz Bello, Shafi'i; Hassan, Rusni (MIR Center for Social-Economic Research, 2013)
Urf or Customary law is one of the most important supporting sources in Islamic law. This can be seen through many legal rulings (ahkam) in Islamic law, which was based on‘urf in which most of these ahkam will change according to the change of circumstances, place and time. As for basis of‘urf or custom, it is the product of the nature of the people and their culture, it grows in strength and popularity by means of imitation that transfers and implants it in the lives of people. Moreover, Contemporary financial system poses great problem and even great challenges to Muslims. Muslims are not permitted by Islamic Law to indulge in ribā. Since contemporary financial system is based on interest, Muslims have great problems in participating in it. Therefore, this paper stands to explain the application of‘urf in Islamic and conventional Bank. The concept and principle of ‘urf in Islamic law was critically analysed such as application of‘urf in Islamic law, differences between ‘urf and consensus of jurists, also between‘urf and adah, in addition, classification of ‘urf, conditions of valid‘urf and so on. Furthermore, the application of‘urf in deposit products under Islamic and Conventional bank were well examined, types of conventional deposit products as well as Islamic deposit products. In fact the product shows that a little different was in-between them which can be easily avoided.